Building Up Atmosphere Can Affect The Incidence Of Anemia In Pregnant Women - Yanti Susan; Neng Titin (Jurnal Kesehatan Mahardika, 2021)
One of the causes bleeding of maternity is anemia. Anemia in pregnancy is anemia due to iron deficiency, this typenof anemia is relatively easy to treat, even cheap. Anemia in pregnancy is a health problem that has high complications for both maternity and fetus. Pregnant women with anemia of more than 50% can cause maternal morbidity and mortality. The research is quantitative research, and using cross sectional design. The population and sample was all pregnant women at Cimanggung village. Sampling used total sampling technique. The type of data collected is primary data. The instrument used is a questionnaire. The analysis used is univariate and bivariate analysis. The results showed that the p value was 0.00< = 0,005, so the resulths showed tha H0 was rejected, meaning that there was a relationship between Establishment of this atmosphere and the incidence of anemia in pregnant women in Cimanggung village. Based on the results of this study it is suggested that midwife always improve building a good atmosphere with the community.